Determinant Factors of Job Satisfaction in Generation Z Informal Workers - Purusa, Nanda Adhi; Riyanto, Fery (Fakultas Ekonomi Universitas Kadiri, 2025)
This study examines the effect of job autonomy, work-life balance, and work-social support on job satisfaction with work motivation as a mediator in informal workers of generation Z in Semarang. The sampling of this study used purposive sampling and data collection techniques with questionnaires for 235 informal workers belonging to Generation Z. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study reveal that job autonomy and work-social support directly and indirectly affect job satisfaction, with work motivation as a mediator. Meanwhile, work-life balance and work motivation directly affect job satisfaction. Work-social support has the most significant effect on work motivation and job satisfaction. This study reveals the importance of building meaningful relationships in the work environment of Generation Z to create a harmonious balance.